2013
DOI: 10.1103/physrevb.88.235315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polarity and hydroxyl termination on the band bending at ZnO surfaces

Abstract: Surface sensitive synchrotron x-ray photoelectron spectroscopy (XPS) and real-time in situ XPS were used to study the thermal stability of the hydroxyl termination and downward band bending on the polar surfaces of ZnO single crystals. On the O-polar face, the position of the Fermi level could be reversibly cycled between the conduction band and the band gap over an energetic distance of approximately 0.8 eV (similar to 1/4 of the band gap) by controlling the surface H coverage using simple ultrahigh vacuum (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
165
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(181 citation statements)
references
References 63 publications
15
165
1
Order By: Relevance
“…The E VBM (2.8–3.3 eV) and Φ (4.1 eV) values found for the sample without water after H* treatment agree very well with published values by Kim et al [35] ( Φ  = 4.08 eV) after Ar + ion sputtering/heating ZnO single crystal at 700 °C, Gutmann et al [19] ( E VBM  = 3.0 eV, Φ  = 4.1 eV) on nanocrystalline ZnO surfaces after annealing at 400 °C in UHV environment, and Heinhold et al [21] ( E VBM  = 3.41 eV) after annealing ZnO single crystal at 750 °C for 15 min. This agreement is not surprising since annealing or Ar + ion sputtering has similar effect of partial cleaning of ZnO as H* treatment.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The E VBM (2.8–3.3 eV) and Φ (4.1 eV) values found for the sample without water after H* treatment agree very well with published values by Kim et al [35] ( Φ  = 4.08 eV) after Ar + ion sputtering/heating ZnO single crystal at 700 °C, Gutmann et al [19] ( E VBM  = 3.0 eV, Φ  = 4.1 eV) on nanocrystalline ZnO surfaces after annealing at 400 °C in UHV environment, and Heinhold et al [21] ( E VBM  = 3.41 eV) after annealing ZnO single crystal at 750 °C for 15 min. This agreement is not surprising since annealing or Ar + ion sputtering has similar effect of partial cleaning of ZnO as H* treatment.…”
Section: Resultssupporting
confidence: 88%
“…Another study by Kumar Kumarappan [20] reported on the effect of H* cleaning on single ZnO (0001) crystal and associated upward band bending after partial removal of the surface contaminants at elevated temperature. Heinhold et al [21] showed the influence of polarity and hydroxyl termination on the band bending at ZnO surfaces. Their results indicated how the Fermi level ( E f ) could be reversibly cycled between the conduction band and the band gap ( E g ) by controlling the surface H coverage using simple ultrahigh vacuum (UHV) heat treatments up to 750 °C, dosing with H 2 O/H 2 and atmospheric exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The plots (b) and (c) show the spatial distribution of the conduction band minimum energy (relative to the Fermi level) when there is an acceptor charge density of 1x10 12 cm -2 and donor charge of density 1x10 13 cm -2 , respectively.Although no surface charge was required to provide agreement between the simulated and experimental results here, the electrostatic condition of the semiconductor surface can affect the transport in nanostructures. This is highly debated for ZnO with many reports showing polar and non-polar ZnO facets in accumulation, while studies of large-area nanowire arrays show a generalized depletion [42][43][44]. The effect on the I-V characteristics of accumulation or depletion of the side and top surfaces of the nanowires is explored through simulations.…”
mentioning
confidence: 99%
“…For comparison, WF data from the literature also measured by various approaches are also shown to provide a perspective of the complexity in comparing WF data also depending on the polarity. WF values from UPS measurements are generally lower (probably because affected by artifacts induced by the UV exposure) than those from theoretical models (which, on the other hand do not take into account defects such as oxygen vacancies and interstitial Zn), although both approaches yielded WF values spread in a wide range. Conversely, C–I and KPFM measurements yielded similar WF values that are also more reproducible in the range 4.6–4.95 eV for the O‐polar and in the range 4.25–4.6 eV for the Zn‐polar, while the WF of the non‐polar (01‐10) ZnO crystal has been reported in the range 4.3–4.64 eV .…”
Section: Resultsmentioning
confidence: 84%
“…(b) Typical 30 × 30 µm 2 surface potential maps with representative line profiles for Zn‐polar ZnO (on the left) and for O‐polar ZnO (on the right) versus the Au reference metal contact. (c) Work function data, WF, measured by KPFM for the different polar ZnO surfaces as‐received samples (blue points), after H 2 plasma (red points) and N 2 plasma (orange points) also compared with data in literature, from UPS measurements (empty black squares), from theoretical models (empty black squares), from C‐I and KPFM measurements …”
Section: Resultsmentioning
confidence: 99%